Co‐introduction of native mycorrhizal fungi and plant seeds accelerates restoration of post‐mining landscapes. Issue 9 (22nd June 2020) - Vahter, Tanel; Bueno, Carlos Guillermo; Davison, John; Herodes, Koit; Hiiesalu, Inga; Kasari‐Toussaint, Liis; Oja, Jane; Olsson, Pål Axel; Sepp, Siim‐Kaarel; Zobel, Martin; Vasar, Martti; Öpik, Maarja
Abstract: Grasslands are among the most threatened terrestrial biomes, and habitat conservation alone will be insufficient to meet biodiversity goals. While restoration of indigenous grasslands is a priority, conflict with economic objectives means that incorporation of alternative habitats is necessary to offset grassland loss. With up to 800, 000 km 2 of land affected by mining globally, there is an opportunity to create additional grassland habitat in post‐mining landscapes. We aimed to assess whether co‐introduction of native arbuscular mycorrhizal (AM) fungi and plants is an efficient means of initializing species‐rich vegetation recovery in barren post‐mining landscapes. We established an experiment in three post‐mining areas in Estonia, where we seeded plots with native plant seeds and inoculated them with trap‐cultured native AM fungi from a similar habitat. We measured the abundance and composition of soil AM fungal and above‐ground plant communities in two consecutive years using relevés, high‐throughput sequencing and fatty acid profiling. Our results demonstrate that co‐introduction of native plants and AM fungi is an effective way to establish species‐rich vegetation in post‐mining areas. Co‐introduction of symbiotic partners resulted in higher richness, diversity and abundance of plants and AM fungi than when either partner was introduced individually. However, the plant and AM fungal communities in sown and inoculated plots were not distinct from those in uninoculated treatments; they rather formed a subset of all taxa present on the sites but exhibited higher diversity than in uninoculated plots. Synthesis and applications . This study shows that managing the below‐ground microbiome is an essential part of vegetation restoration. The availability of symbiotic partners can be considered a key aspect determining the diversity of restored vegetation. Targeted inoculations with native and habitat‐specific native arbuscular mycorrhizal fungi could therefore increase restoration success. Abstract : This study shows that managing the below‐ground microbiome is an essential part of vegetation restoration. The availability of symbiotic partners can be considered a key aspect determining the diversity of restored vegetation. Targeted inoculations with native and habitat‐specific native arbuscular mycorrhizal fungi could therefore increase restoration success.